Effects of an EMR Education Program on Nursing Information Literacy, Self-Directed Learning, Problem-Solving Ability, and Practice Satisfaction of Undergraduate Nursing Students. - Dongwon Choi (Journal of Korean Academy of Fundamentals of Nursing, 2024)
Purpose: This study implemented an electronic medical record (EMR) training program for nursing students and aimed to confirm its effectiveness. Methods: A non-equivalent control group pretest-posttest design was used. The participants were 42 sophomore nursing students enrolled in a fundamental nursing course (experimental group: n=21, control group n=21). The EMR training program consisted of 6 sessions, taught over 5 weeks. Data were collected between April 23 and July 14, 2023, and were analyzed using the χ² test, Fisher exact test, t-test, paired t-test, Wilcoxon signed-rank test, and Mann-Whitney U test with SPSS for Windows version 24.0. Results: Significant differences were shown between the experimental and control groups regarding self-directed learning ability (t=2.22, p=.032), problem-solving ability (t=2.34, p=.026), practice satisfaction (U=136.00, p=.016) and EMR competency (U=101.50, p=.001). Conclusion: The EMR training program effectively improved nursing students' self-directed learning ability, problem-solving ability, practice satisfaction, and EMR competency. Therefore, developing and applying EMR-related content can enhance nursing student's awareness of EMR systems is recommended.